2020
DOI: 10.1111/imr.12839
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes contributing to inflammation in arthritis

Abstract: Inflammasomes are intracellular multiprotein signaling platforms that initiate inflammatory responses in response to pathogens and cellular damage. Active inflammasomes induce the enzymatic activity of caspase‐1, resulting in the induction of inflammatory cell death, pyroptosis, and the maturation and secretion of inflammatory cytokines IL‐1β and IL‐18. Inflammasomes are activated in many inflammatory diseases, including autoinflammatory disorders and arthritis, and inflammasome‐specific therapies are under de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 162 publications
(317 reference statements)
1
97
0
1
Order By: Relevance
“…Another way to modulate the innate immune response is to regulate the activation of particular inflammasomes ( Broz and Dixit, 2016 ; Ding et al, 2019 ; Spel and Martinon, 2020 ). Among various types of inflammasomes, nucleotide-binding domain and leucine-rich-repeat-containing family and pyrin domain-containing 3 (NLRP3) is implicated in Alzheimer’s disease and type 2 diabetes upon aberrant activation.…”
Section: Application In Inflammation Regulationmentioning
confidence: 99%
“…Another way to modulate the innate immune response is to regulate the activation of particular inflammasomes ( Broz and Dixit, 2016 ; Ding et al, 2019 ; Spel and Martinon, 2020 ). Among various types of inflammasomes, nucleotide-binding domain and leucine-rich-repeat-containing family and pyrin domain-containing 3 (NLRP3) is implicated in Alzheimer’s disease and type 2 diabetes upon aberrant activation.…”
Section: Application In Inflammation Regulationmentioning
confidence: 99%
“…IL-1β is a kind of pro-in ammatory cytokines,to a certain extent,production and release of IL-1β can resistance infection,but at the same time,there are correlations with gout,rheumatoid arthritis,chronic kidney disease,atherosclerosis and so on [27][28] .Studies have demonstrated that [29] IL-1β can promote the recruitment of neutrophil in the part of in ammation so that cause gout.In addition,IL-1β can make the person produces strong pain by activation injured receptor which exist in peripheral sensory nerve system sensitively and directly.The processing and secretion of IL-1β not only can through NOD-like receptor signaling pathways,but also can by Toll-like receptor signaling pathways.When MSU crystals are identi ed by Toll-like receptor,TLRs are able to interact with MyD88,make the MyD88 activation,leading to the activation of nuclear factor kappa B (NF-κB) and enter the nucleus to produce IL-1β,cause in ammation eventually through the cascade ampli cation effect [30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it resembles the inflammatory syndromes that may complicate anti-phospholipid antibody syndrome (APS), namely the catastrophic anti-phospholipid syndrome (CAPs), characterized by disseminated intravascular microthrombosis [29]; or, the systemic CLLS characterized by altered capillary wall permeability [30]. Besides CAPs and CLLS, the SARS-CoV-2 inflammation, leading to ARDS, shares pathogenic mechanisms and clinical-radiological aspects with other auto-immune/-inflammatory diseases, such as juvenile idiopathic arthritis and its adult form [31][32][33] and Kawasaki disease [34]. Systemic CLLS has also been observed in Kawasaki disease [35].…”
Section: Pathology and Laboratory Evidence Of Clls And Inflammationmentioning
confidence: 99%